White matter properties in fronto-parietal tracts predict maladaptive functional activation and deficient response inhibition in ADHD - Daniel Smullen; Andrew P. Bagshaw; Lilach Shalev; Shlomit Tsafrir; Tamar Kolodny; Carmel Mevorach (Scientific Reports)
Abstract Response inhibition is a key characteristic of adaptive human behaviour. However, in attention deficit hyperactivity disorder (ADHD) it is often impaired. Previous neuroimaging investigations implicate a myriad of brain networks in response inhibition, making it more difficult to understand and overcome response inhibition difficulties. Recently, it has been suggested that a specific fronto-parietal functional circuitry between the inferior frontal gyrus (IFG) and the intraparietal sulcus (IPS), dictates the recruitment of the IPS during response inhibition in ADHD. To ascertain the critical role of the IFG-IPS functional circuit and its relevance to response inhibition in ADHD, it is crucial to understand the underlying structural architecture of this circuit so that the functional relevance could be interpreted correctly. Here we investigated the white matter pathways connecting the IFG and IPS using seed-based probabilistic tractography on diffusion data in 33 ADHD and 19 neurotypicals, assessing their impact on both IPS recruitment during response inhibition and on response inhibition performance in a Go/No-go task. Our results showed that individual differences in the structural properties of the IPS-IFG circuit, including tract volume and diffusivity, were linked to IPS activation and even predicted response inhibition performance outside the scanner. These findings highlight the structural-functional coupling within the IFG-IPS circuit in response inhibition in ADHD and suggest a structural basis for maladaptive functional top-down control in deficient inhibition in ADHD.